Temperature and time-dependent behaviour of a water base mud treated with maize (zea mays) and cassava (manihot esculanta) starches (2015)
Starch, one of the commonly used additives in drilling fluids, degenerates with time under cyclic temperature and pressure loads, causing changes in mud properties. This study was designed to establish the effect of temperature and aging on water base mud treated with starches prepared from maize (Zea mays) and cassava (Manihot esculanta) starches. The effect of potash and tannathin on the muds was also investigated. Plastic viscosity of treated samples at varying temperatures (24.4, 40.0, 60.0 and 80.0 O C) was determined using standard API practices over a period of 72 hours. At ambient conditions, the plastic viscosity of samples treated with maize and cassava varied between 5 and 7 cp and increased to between 6 and 12 cp when the samples were further treated with potash. Plastic viscosity for industrial starch varied from between 5 and 6 cp but increased to between 7 and 10 cp when further treated with potash. Predictive models for plastic viscosity and yield point gave coefficient of variance between 90 and 92% respectively. However, all the starches degenerated within 24 hours and would require further treatment to prevent biodegradation.